A Review: IoT Based Camera Surveillance System - Rani, Ritu; Indora, Sanjeev (International Journal of Computer Sciences and Engineering, 2019)
IOT based Security systems are developed for keeping money safe. In this research objective is to provide more security to the physical wallet with reduced storage cost. The proposed model is capable to solve issues related to expenses and performance. Research is supposed to provide security at remote location without requirement of human attention with help of graphical processing. This research would establishment of cloud environment to host application. Implementation of frame capturing module works from two different dimensions to too boost the security. The size of captured frame sample would be reduced in order to save the storage space. Applying Edge detection mechanism would allow fetching only comparable information make system fast.